â€œ EFEK PENGGUNAAN STRATEGI PEMBELAJARAN KUANTUM PADA MATA KULIAH SPEAKING MAHASISWA PRODI PENDIDIKAN BAHASA INGGRIS FKIP UNSIKAâ€ - Wigati, Fikri Asih (Majalah Ilmiah SOLUSI, 2011)
Teachers often face the problem of having lack creativity regarding the innovative teaching strategy and method in speaking. Therefore the research was aimed to know the effect of Quantum Teaching Strategy ( QTS) on the studentâ€™s performance of English Speaking Skill in comparison to Conventional Teaching Strategy ( CTS) to have the clear portrait of the QTSâ€™ advantage. The quantitative research was to measure the pertaining effects of QTS on the Speaking performance. The data was taken from an experimental research, involving 30 students in UNSIKA (Singaperbangsa Karawang University) in the English Education program. The 2nd semester students were randomly selected. 29 students run learning activity with quantum learning method and 26 students studied in control group. The experimental group got particular treatments related to quantum learning method. The treatment for the experimental group was to improve their speaking skill. The control group was taught in conventional teaching strategy. Both groups pretest and post test to identify their performance on the speaking skill improvement. The measurement for both groups was conducted at the same test. In term of quantitative approach, quasi experiment design was used to describe the different result of experimental group and control group. T-test was used to analyze the data to measure the effect of quantum teaching strategy in comparison to Conventional Teaching Strategy ( CTS). By means of The T Test, the finding showed that QTS affected the performance of English Speaking skill. It is recommended for English Teacher to use QTS as alternative to improve quality of teaching.